Assessment of soil physical attributes at sowing row and inter-row under no-till system - Blum, Julius; Giarola, Neyde Fabíola; da Silva, Álvaro; Guedes Filho, Osvaldo; Silva, Sâmala Glícia; Eberhardt, Diogo; Araújo, Suzana (Revista Ciência Agronômica, 2014)
In no-till systems, two different soil conditions are created during the sowing operation: row and inter-row positions. The objectives of this study were to evaluate, using static and dynamic soil attributes, the influence of no-till sowing operation on creating better physical environment for soybean crop growth. A field transect with clay content ranging from 150 to 400 g kg-1 was selected in Ponta Grossa, Paraná State, Brazil, from a Typic Hapludox that has been cultivated under no-till system for 16 years. After soybean harvest, 68 undisturbed soil samples were collected at both sowing row and inter-row positions. The following soil properties were evaluated: saturated hydraulic conductivity, air permeability, bulk density, total porosity, soil moisture at field capacity, texture, and total organic carbon. Multiple regressions among dynamic and static soil properties were fitted, and differences between sowing row and inter-rows were tested by paired t test. Saturated hydraulic conductivity and air permeability were positively correlated with macroporosity (r = 0.75 and 0.74, respectively; p